2005
DOI: 10.1016/j.ultsonch.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound promoted regioselective synthesis of β-iodoethers from olefin-I2-alcohol

Abstract: Regioselective synthesis of b-iodoethers in high yields by sonicating alkene and alcohol in the presence of iodine in a bath at 35 kHz is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Markovnikov-type vicinal iodohydrins, iodoethers or iodoacetates (120) were obtained by treatment with molecular iodine in the presence of sources of various nucleophiles (OH, OR, OAc, F). Its activation was performed by different metallic ions in salts 83a or natural clay 84 (entries 1, 2), by itself in excess 83b (entry 3), acetic acid 86 (entry 4), ultrasound 87 (entry 5), or anionic surfactant 88 (entry 6), while oxidative activation using cerium(IV) 89a (entry 7), zinc(II) chloride (entry 8), 89b hypervalent iodine(III) derivatives 90 (entries 9-11), or 30% aqueous hydrogen peroxide 91,92 (entries 12, 13) was also employed.…”
Section: Iodination Of Alkenes and Alkynesmentioning
confidence: 99%
“…Markovnikov-type vicinal iodohydrins, iodoethers or iodoacetates (120) were obtained by treatment with molecular iodine in the presence of sources of various nucleophiles (OH, OR, OAc, F). Its activation was performed by different metallic ions in salts 83a or natural clay 84 (entries 1, 2), by itself in excess 83b (entry 3), acetic acid 86 (entry 4), ultrasound 87 (entry 5), or anionic surfactant 88 (entry 6), while oxidative activation using cerium(IV) 89a (entry 7), zinc(II) chloride (entry 8), 89b hypervalent iodine(III) derivatives 90 (entries 9-11), or 30% aqueous hydrogen peroxide 91,92 (entries 12, 13) was also employed.…”
Section: Iodination Of Alkenes and Alkynesmentioning
confidence: 99%
“…In continuation of our work on the development of efficient and environmentally friendly methods for the synthesis of various organic compounds [28][29][30][31][32][33], in this paper the study of the activity of nano-MgO as a novel and eco-friendly heterogeneous catalyst for the N-formylation of various amines by formic acid under solvent-free microwave irradiation is presented (Scheme 1). For comparison, bulk-MgO catalysts were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…We feel that, the electron-donating groups present on the arene nucleus destabilize the o-QM intermediate towards the 1,4-nucleophilic addition reaction and hence, the reaction is slower and gives low yield of the desired products. Satisfied with the above results, we extended the reaction of b-naphthol and aromatic aldehydes with benzamide instead of acetamide to get the respective products in high yield in the presence of catalytic amounts of silica chloride under sonic condition, and the results of this study are also presented in Table 2 (entries [16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 83%
“…Frequencies below 50 kHz are generally preferred for the heterogeneous systems due to the more intense mechanical effects [18b]. Hence, we selected 35 kHz for maximum sonication, and from our laboratory we have already reported the use of ultrasound in various reactions like synthesis of d-chloroesters [19] and b-iodoesters [20]; reduction of nitroarenes into arylamines [21] and reduction of aryl nitro compounds to azo arenes or arylamines [22] Li et al have reported a Biginelli-type reaction to synthesize the 3,4-dihydropyrimidin-2-ones catalyzed by NH 2 SO 3 H under sonic condition [23].…”
Section: Introductionmentioning
confidence: 99%